A novel GC-rich dispersed repeat sequence in Drosophila melanogaster. - Flavell, A; Dyson, J; Ish-Horowicz, D (1987)
A novel family of dispersed repeat sequences from Drosophila melanogaster is described. Sequence analysis of two members of this family show them to contain greater than 75% GC bases. These are comprised of multiple repeats of GGX triplets interspersed occasionally with CGPy and TTPy. Southern blotting shows that these repeats are not transposable elements. Twenty four homologous recombinants have been localised by in situ hybridization to seven sites in the Drosophila genome. Polyadenylated RNAs homologous to this repeat family are expressed in a complex pattern which is developmentally regulated. We suggest that this family encodes a set of glycine-rich domains in Drosophila proteins.